Participation of the Government in the legislative process of the Republic of Kazakhstan - Zheksekin, A.K. (Bulletin of the Karaganda University “Law Series”, 2022)
The article consists in the fact that a multidimensional and systematic study of one of the important problems of legal science, which has both theoretical and applied significance, has been conducted — the issues of participation of the Government of the Republic of Kazakhstan in the legislative process. The study is aimed, on the one hand, at enriching theoretical thought in the field of development and adoption of laws, and on the other hand, at improving the system of normative legal acts of the Republic of Kazakhstan in the field of participation of the Government of the Republic of Kazakhstan in the legislative process. The novelty of the topic of this article lies in the fact that the activity of the state in issuing laws in modern conditions is closely related to the general functions of the state. On the one hand, such activity acts as a reflection and specification of the internal functions of the state, and on the other hand, it is an indicator of its own immanent properties and political and managerial capabilities in the organization of the legislative process, expressing the independence of the legislative functions of the state. Taking into account all these factors, it is necessary to optimize and improve the participation of the Government of the Republic of Kazakhstan in the legislative process. Thus, in the address of the president of the Republic of Kazakhstan K.-ZH. Tokayev to the people of Kazakhstan on September 2, 2019, «the government will have to adapt legislation to new technological phenomena: 5G, Smart Cities, Big Data, Blockchain, digital assets, new digital financial instruments». The solution of these and other tasks in the field of Government participation in the legislative process largely depends on the degree of scientific elaboration of this issue. In this regard, the study of theoretical issues and a detailed analysis of the practice of the participation of the Government of the Republic of Kazakhstan in the legislative process is of great interest, because, as the MPs themselves note, «practice shows that the Government is the most active participant in the legislative process, since the vast majority of bills are developed by the Government».